Te vacancy-driven superconductivity in orthorhombic molybdenum ditelluride. (5th June 2017) - Cho, Suyeon; Kang, Se Hwang; Yu, Ho Sung; Kim, Hyo Won; Ko, Wonhee; Hwang, Sung Woo; Han, Woo Hyun; Choe, Duk-Hyun; Jung, Young Hwa; Chang, Kee Joo; Lee, Young Hee; Yang, Heejun; et al.
Abstract: Two-dimensional (2D) transition metal dichalcogenides (TMDs) have received great attentions because of diverse quantum electronic states such as topological insulating (TI), Weyl semimetallic (WSM) and superconducting states. Recently, the superconducting states emerged in pressurized semimetallic TMDs such as MoTe2 and WTe2 have become one of the central issues due to their predicted WSM states. However, the difficulty in synthetic control of chalcogen vacancies and the ambiguous magneto transport properties have hindered the rigorous study on superconducting and WSM states. Here, we report the emergence of superconductivity at 2.1 K in Te-deficient orthorhombic T d -MoTe2− x with an intrinsic electron-doping, while stoichiometric monoclinic 1T′-MoTe2 shows no superconducting state down to 10 mK, but exhibits a large magnetoresistance of 32 000% at 2 K in a magnetic field of 14 T originating from nearly perfect compensation of electron and hole carriers. Scanning tunnelling spectroscopy and synchrotron x-ray diffraction combined with theoretical calculations clarify that Te vacancies trigger superconductivity via intrinsic electron doping and the evolution of the T d phase from the 1T′ phase below 200 K. Unlike the pressure-induced superconducting state of monoclinic MoTe2, this Te vacancy-induced superconductivity is emerged in orthorhombic MoTe2, which is predicted as Weyl semimetal, via electron-doping. This chalcogen vacancy induced-superconductivity provides a new route for cultivating superconducting state together with WSM state in 2D van der Waals materials.